2003
DOI: 10.1159/000068556
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Epiretinal Membrane with Indocyanine-Green-Assisted Peeling

Abstract: Purpose: To evaluate the surgical results of pars plana vitrectomy with peeling of the inner limiting membrane (ILM) in a preliminary series of 28 eyes with macular epiretinal membrane (ERM). Methods: Pars plana vitrectomy with peeling of the ERM was performed on 28 eyes. All preretinal macular tissues were removed including the ILM after injection of indocyanine green (ICG) solution. Results: Postoperatively visual acuity improved within 3 months by at least 2 lines in 26 eyes. Neither the deterioration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…Surgeons have reported injectable ICG concentrations of between 0.025 and 0.5% (table 1) [10,11,12, 14, 40, 43, 44, 47, 51, 52,80,81,82,83]. Kwok et al [51] recently compared the intensity of ILM staining after ICG injection in three different concentrations (0.25, 0.5 and 1.25 mg/ml) and found that the highest injections (1.25 mg/ml) offered the best visualization of the ILM.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Surgeons have reported injectable ICG concentrations of between 0.025 and 0.5% (table 1) [10,11,12, 14, 40, 43, 44, 47, 51, 52,80,81,82,83]. Kwok et al [51] recently compared the intensity of ILM staining after ICG injection in three different concentrations (0.25, 0.5 and 1.25 mg/ml) and found that the highest injections (1.25 mg/ml) offered the best visualization of the ILM.…”
Section: Surgical Techniquementioning
confidence: 99%
“…5,6 Bazı araştırmacılar, indosiyanin yeşili (İSY) kullanılarak uygulanan ERM ile birlikte İLM soyulmasının, görme keskinliğinde artış ve ERM nüksünde azalma sağladığını ileri sürmüşlerdir. [6][7][8] Ancak İSY'nin çeşitli toksik etkileri bildirilmiş ve İLM boyanmasında kullanımı giderek azalmıştır. 9 Son yıllarda, ERM cerrahisinde yalnızca tripan mavisi (TM) ve diğer boyalarla birlikte çift boyama yöntemi ile brilliant mavisi (BM) kullanılmaya baş-lanmıştır.…”
unclassified
“…Recently, Sorcinelli [1] has reported his experience with pars plana vitrectomy plus indocyanine green (ICG)-guided internal limiting membrane (ILM) peeling in a series of 28 patients with macular epiretinal membrane (ERM). The author injected ICG in a concentration of 0.5% over the macula.…”
mentioning
confidence: 99%
“…First, Sorcinelli [1] exposed the retina for 5 min to ICG. We believe that this exposure time is too long, since it may increase the risk of ICG toxic effects to the RPE and other layers of the retina.…”
mentioning
confidence: 99%
See 1 more Smart Citation